Effect of Microfinance on Enterprise Level of Poor People: An Empirical Study - Parajuli, Ram prasad (Journal of Advanced Academic Research, 2017)
The current study tries to set the impact of micro-credit services on improvement in business base in Nepal. The study employed a causal study. The sample for this study consists of participants of MFIs in the Kathmandu, Lalitpur and Sindhupalchok from January 2014 to December January 2016. Stratified random sampling was used to select 400 respondents. Data was collected by use of a questionnaire and in-depth interview. The data was pre-processed using Statistical Package for Social Sciences (SPSS). Studies shows the credit facilities had the highest impact followed by use of different business base. The study also recommends that the MFIs operating in the Nepal be empowered through provision of finances which can be advanced to the locals as credit to facilitate economic growth of people. To build capacity among the people of the study area, the study recommends that the MFIs operating in the Nepal undertake regular training especially on financial management/ management as well as operational courses so that the local can learn the best financial management skills and thus improve their businesses as well as income. Journal of Advanced Academic Research, Vol. 3, No.3, 2016, page:22-30